Onosma bracteatum wall: A Potent analgesic agent (Bangladesh Journal of Medical Science, 2018)
Background: This study was aimed to find out the central and peripheral analgesic activity of hydro methanolic extract of aerial parts of Onosma bracteatum.Material and methods: The central and peripheral analgesic activity is evaluated by tail flick test and acetic acid induced writhing test at the doses of 50, 100, 250 and 500mg/kg body weight respectively in animal models.Results: The results obtained from Tail flick test revealed that O. bracteatum possesses potent analgesic effects by inducing significant increase in latency period in dose dependent manner at all doses at 1, 2 and 3 hours post feeding respectively. The maximum effect was observed at a dose of 500mg/kg i.e. 258.9% (p